Examining the role of digital economy on supply chain resilience: an empirical analysis of China's food sector - Ding, Zhao; Yue, Hongxia; Liu, Jiawei (Frontiers in Sustainable Food Systems, 2025)
IntroductionIn the digital economy era, the application of digital technologies plays a crucial role in strengthening the food supply chain, especially in ensuring food security. The study of how the digital economy impacts the resilience of the food supply chain is of great practical significance.MethodsBased on provincial data from China from 2008 to 2023, this research employs fixed effect, mediation effect, and threshold models. These models are utilized to explore the mechanism through which the digital economy improves the resilience of the food supply chain.ResultsThe findings indicate that the digital economy has a significant positive effect on enhancing the resilience of the food supply chain. This positive relationship remains stable even after considering potential endogeneity problems. Specifically, the impact of the digital economy is more prominent in major food—producing regions, showing their advantages in using digital development to boost supply chain stability and efficiency. Additionally, information technology adoption acts as an important mediating factor in the relationship between the digital economy and supply chain resilience, and there is a threshold effect of fiscal investment in science and technology on the impact of the digital economy on supply chain resilience.DiscussionThe results suggest that to fully utilize the potential of the digital economy, accelerate the digital and intelligent upgrade of the food supply chain, strengthen its resilience, and promote high—quality agricultural development, the government should take actions. These include accelerating the construction of digital infrastructure, promoting the digital transformation of the food industry, strengthening regional cooperation, and enhancing the resilience of the food supply chain to ensure food security.